Sudden Death as a Complication of Choriocarcinoma. Issue 1 (3rd August 2014) - Das, Siddhartha; Badhe, Bhawana; Bibi, Asma; Mohanty, Manoj K.
Abstract We report the case of a young man with a history of sudden death. On autopsy, a large retroperitoneal mass was found along with secondaries in the liver and lungs. No testicular abnormality was detected on palpation. Based on histopathological examination, it was diagnosed to be a case of choriocarcinoma. Unfortunately, it was not definitively determined whether the retroperitoneal mass represents the primary tumor or secondary involvement with testes being the primary source. It is important that forensic pathologists are aware of this disease as a potential cause of sudden death. The main focus of the paper is the approach of a forensic pathologist to a case of a sudden death when an unexpected and undiagnosed tumor is found in the retroperitoneum and not much information is available about the clinical history of the deceased.